RbNb6Cl12O2: CRYSTAL STRUCTURE AND MAGNETIC PROPERTIES - Fakhili Gulo (Indonesian Journal of Chemistry, 2008)
A novel niobium oxychloride cluster compound, RbNb6Cl12O2 was obtained by solid state synthesis from stoichiometric mixture of RbCl, Nb2O5, NbCl5 and Nb powder, heated at 675 °C. Its structure was determined by single-crystal X-ray diffraction. It crystallizes in the monoclinic system (a = 6.8097(4) Å, b = 11.6700(9) Å, c = 12.5090(9) Å, ß = 101.337(4) °, V = 974.68(12) Å3, and Z = 2) with the space group of P21/c. The cluster framework of this compound is based on  units connected via oxide ligands in the a-direction with two Nb-O linkages between adjacent clusters, which resembles intercluster bonding in Chevrel-Sergent phases. In the other two directions, the linkages occur through single Cla-a bridges. The framework generates channels where the cations Rb+ are located. This compound contains valence electron concentration (VEC) of 15 per cluster unit and therefore exhibits the paramagnetic behavior.